(untitled) (Raparin Journal of Humanities (RJH), 2021)
The purpose of this research is:- • Knowing the role of television in creating anxiety among students in general. • Knowing the role of television in creating anxiety among students according to gender change. • Knowing the role of television in creating anxiety among students according to the changing stages Researchers have prepared a scale for conducting their research, the most important of which is the statistics used, including SPSS person and t-tests. The most important results of the study have shown that television plays a role in creating anxiety by the study participants. There are no differences according to gender and different stages. Thus, at the result, this research eventually came up with some suggestions: monitoring TV shows and limiting the presentation of programs that cause fear and anxiety to the audience. • Providing the psychological and social researchers on the television staff to evaluate and bowdlerize any programs before broadcasting. • Knowing the television efforts to postpone programs that cause fear and anxiety when they are promoted. • Monitoring the dramas performed on some channels, because some of them are incompatible with culture and social values, will cause fear and anxiety for the audience.